Henoch-Schönlein Purpura Nephritis in Children: A Review (Bangladesh Journal of Child Health, 2014)
Henoch-Schönlein purpura (HSP) is a systemic disorder which involves multiple organs including kidney. The characteristic pathology is leukocytoclastic vasculitis of the capillaries with deposition of IgA immune complexes. The principal cause of morbidity and mortality in this disease is due to renal involvement. Approximately half of the children with HSP develop nephritis (HSPN) within 4-6 weeks of initial presentation and HSPN is a major cause of end stage renal disease (ESRD) in children. So, it is important to be updated about aetio-pathogensis, clinico-pathological aspects and prognostic factors of nephritis related to Henoch Schonlein purpura. The most important is to identify the appropriate treatment options for HSPN. So, herein review has been done on the different aspects of HSPN including treatment. DOI: http://dx.doi.org/10.3329/bjch.v38i1.20024 Bangladesh J Child Health 2014; VOL 38 (1) : 24-31